Enhanced oral bioavailability and bioefficacy of phloretin using mixed polymeric modified self‐nanoemulsions. Issue 7 (28th May 2020) - Wang, Yiling; Li, Dongli; Lin, Huiqiong; Jiang, Sen; Han, Lei; Hou, Shuli; Lin, Shuying; Cheng, Zhefeng; Bian, Wangqing; Zhang, Xinxin; He, Yan; Zhang, Kun
Abstract: Phloretin (Ph) is a natural active ingredient with wide biological properties. However, its poor water‐solubility and low oral bioavailability limit the application significantly in functional food and drug. This study was to explore the mixed polymer Pluronic® F127 and P123 modified the different triglycerides (LCT, MCT, SCT) in self‐nanoemulsions (SNEs) for enhancing the oral bioavailability and bioefficacy of Ph. The SNEs were characterized in terms of physical property study, lipolysis study, pharmacokinetic study, and anti‐inflammatory effect. The water‐solubility of LCT‐Ph‐SNE increased 3000‐fold compared with Ph solution. Pharmacokinetic study of SNEs and other carriers (HP‐β‐CD, PVP) results indicated that LCT‐Ph‐SNE was 7.9‐fold more bioavailable compared with unformulated Ph. The anti‐inflammatory activity of LCT‐Ph‐SNE in vivo represented a 6.8‐fold enhancement compared with unformulated Ph. This novel SNE formulation may also be used for other poorly soluble ingredients with high loading capacity, which made a significant impact on functional food and drug. Abstract : A novel self‐nanoemulsions modified by mixed polymers are effective in enhancing the bioavailability of phloretin (Ph). The mixed polymer modified self‐nanoemulsions (SNEs) to minimize the degradation clearance by enzymes in mucus. Enhance the oral bioavailability and bioefficacy of poorly soluble ingredients phloretin (Ph). The water‐solubility and oral bioavailability of LCT‐Ph‐SNE has significantly increased. The anti‐inflammatory activity of LCT‐Ph‐SNE in vivo is much higher that the unformulated Ph.